Plant growth regulators to enhance fruit color of 'Gala' apples - Brighenti A.F. (2017)
The objective of this work was to investigate the effect of plant growth regulators for enhancing fruit color of 'Gala Standard' apples (Malus domestica). The experiment was carried out in the 2015 and 2016 crop seasons. The treatments consisted of water, as a control; 300 mg L-1 ethephon, as a positive control; 400 mg L-1 prohydrojasmonate; and 400 mg L-1 abscisic acid. Flesh firmness, soluble solids content, fruit weight, and red color were assessed after harvest. Plant growth regulators enhanced red color of fruit and chlorophyll degradation. Prohydrojasmonate and abscisic acid did not reduce flesh firmness, in the 2016 season.